Implementation of Waitress Performance in Service at Feast Restaurant Sheraton Bandung Hotel and Towers - Hernanda, Seviani (STKIP Singkawang, 2024)
This study discusses how to implement the performance of waiters in providing services at the Feast Restaurant Sheraton Bandung Hotel and Towers. The performance of the waiter is the key to the success of the service in the restaurant because it is closely related to the quality of the service to be able to compete with other restaurants. In this case, the duties and responsibilities of the waiter are needed so that they can be carried out properly. This strategy was created as a reference for dealing with the constraints that exist at the Feast Restaurant Sheraton Bandung Hotel and Towers. In this study, the authors used qualitative methods with the type of data collection observation, interviews, and literature. The results of this study were expected to contribute to the servers at the Feast Restaurant Sheraton Bandung Hotel and Towers in carrying out their operations.